Relationship Marketing, Customer Experience and Customer Satisfaction: Testing Their Theoretical and Empirical Underpinning - Suharto Suharto; Arber Hoti (Jurnal Manajemen Bisnis, 2023)
Research aims: This study’s aim is to find out the influence of relationship marketing on customer experience and satisfaction.Design/Methodology/Approach: The applied research method of this study uses an explanatory survey utilizing accidental sampling of 140 respondents in the Rural Bank industrial sector, Lampung Province - Indonesia. Data is scrutinized utilizing the structural equation to test the proposed hypothesis. Research findings: The results found that (1) relationship marketing directly and positively affected customer experience and customer satisfaction, and (2) customer experience directly and positively impacted customer satisfaction.Theoretical Contribution/Originality: Customer satisfaction is the end of the chain that must be maintained to gain the sustainability of organizations. By emphasizing customer relationship quality and customer experience, it would strive to maintain transaction processes and strategies to impress customer satisfaction with the organizations.Practitioners/Policy Implications: Relationship marketing and customer experience are relevant concepts in marketing research because properly understanding these variables enables organizations to increase customer satisfaction and achieve a competitive advantage in the service and manufacturing sectors.Research Limitations/Implications: This research model was tested in the rural banking industry sector, Lampung Province - Indonesia, so the findings obtained limit generalization. Therefore, using longitudinal data, it is necessary to conduct a comparative and comprehensive study between relationship marketing, customer experience, and customer satisfaction.